Bactofencin A, a New Type of Cationic Bacteriocin with Unusual Immunity - Eileen F. O'Shea (American Society for Microbiology, 2013)
ABSTRACT Bacteriocin production is an important probiotic trait of intestinal bacteria. In this study, we identify a new type of bacteriocin, bactofencin A, produced by a porcine intestinal isolate Lactobacillus salivarius DPC6502, and assess its potency against pathogenic species including Staphylococcus aureus and Listeria monocytogenes. Genome sequencing of the bacteriocin producer revealed bfnA, which encodes the mature and highly basic (pI 10.59), 22-amino-acid defensin-like peptide. Matrix-assisted laser desorption ionization–time of flight (MALDI-TOF) mass spectral analysis determined that bactofencin A has a molecular mass of 2,782 Da and contains two cysteine residues that form an intramolecular disulfide bond. Although an ABC transporter and transport accessory protein were also present within the bacteriocin gene cluster, a classical bacteriocin immunity gene was not detected. Interestingly, a dltB homologue was identified downstream of bfnA. DltB is usually encoded within the dlt operon of many Gram-positive bacteria. It is responsible for d-alanylation of teichoic acids in the cell wall and has previously been associated with bacterial resistance to cationic antimicrobial peptides. Heterologous expression of this gene conferred bactofencin A-specific immunity on sensitive strains of L. salivarius and S. aureus (although not L. monocytogenes), establishing its role in bacteriocin immunity. An analysis of the distribution of bfnA revealed that it was present in four additional isolates derived from porcine origin and absent from five human isolates, suggesting that its distribution is host specific. Given its novelty, we anticipate that bactofencin A represents the prototype of a new class of bacteriocins characterized as being cationic, with a DltB homologue providing a cognate immunity function. IMPORTANCE This study describes the identification, purification, and characterization of bactofencin A, a novel type of bacteriocin produced by L. salivarius DPC6502. Interestingly, bactofencin A is not similar to any other known bacteriocin but instead shares similarity with eukaryotic cationic antimicrobial peptides, and here, we demonstrate that it inhibits two medically significant pathogens. Genome sequence analysis of the producing strain also revealed the presence of an atypical dltB homologue in the bacteriocin gene cluster, which was lacking a classical bacteriocin immunity gene. Furthermore, cloning this gene rendered sensitive strains resistant to the bacteriocin, thereby establishing its role in providing cognate bacteriocin immunity. Four additional L. salivarius isolates, also of porcine origin, were found to contain the bacteriocin biosynthesis genes and successfully produced bactofencin A, while these genes were absent from five human-derived strains investigated.